Boredom, Cyberloafing, And Perceived Justice Affect Performance Of Generation Y And Generation Z, In Indonesia’s Logistics Sector: Mediating Role Of Organizational Commitment - Dedianto Turnip; Bahtiar Usman; Deasy Aseanty (CV. AFDIFAL MAJU BERKAH, 2026)
This quantitative research aims to examine the influence of job boredom, cyberloafing, and perceived organizational justice on performance of generation Y and Z, with the mediation of organizational commitment in the logistics sector of warehousing and land transportation in Indonesia. The cross-sectional approach was used in data collection with purposive sampling, by distributing questionnaires to employees, working in 8 logistics companies in Jakarta during October until November 2024, with 1014 respondents involved, 623 generation Y and 391 generation Z. Data analysis is using Structural Equation Modeling. The results of the hypothesis test show there is no direct influence of cyberloafing or through the mediation of organizational commitment on employee performance, but there is mediation of organizational commitment in the influence of job boredom and perceived organizational justice on employee performance. This study contributes to the enrichment of literature on the work behavior of generation Y and generation Z regarding job boredom, perceived organizational justice, cyberloafing, and organizational commitment in association with performance. Companies need to strive on strengthening organizational values and culture that can inspire employees, as well as creating policies and activities that can strengthen organizational commitment, so that they can mitigate the negative impact of job boredom and increase the positive influence of perceived organizational justice on employee performance. Future research should study the frequency of cyberloafing and longitudinal test that can lead to more comprehensive analysis.